Konflik Antar Budaya dan Antar Etnis di Indonesia Serta Alternatif Penyelesaiannya - Najwan, Johni (Jurnal Hukum IUS QUIA IUSTUM, 2016)
Multi cultures are potentially threatening national integrity as inter cultural conflict will lead to conflicts of inter ethnical, inter-believer, interracial, or even inter groups which are very sensitive and vulnerably leading to national disintegration. This phenomenon can emerge if the conflict is not controlled and well resolved. The research asked a question first, to what extent can law function as the social control system? Second, what is the alternative solution for resolving intercultural and inter ethnical conflict in Indonesia? The research found the following results: First, Law Function. Besides working as the means to control social order, the social control also is used as the means to prepare the social life of society. Second, as one alternative to solve such conflicts, we need deeper understanding concerning function and role of law in multi cultural and multi ethnical social life . Therefore, the paradigm problem in terms of national law development by government should be learned more comprehensively. Key words : Inter cultural conflict, inter ethnical conflict, alternative solution